Edge Computing for Internet of Things (IoT) System on Battery Monitoring System (BMS) to Determine State of Charge (SoC) and State of Health (SoH) - Mulyana, Agus; Ferdiansyah, M I (International Journal of Research and Applied Technology (INJURATECH), 2023)
The purpose of this study is to measure the State of Charge (SoC) and State of Health (SoH) of the VRLA battery. The method used in this study was to combine the internal parameters of each battery, namely current, voltage, and internal resistance, while the external parameters are temperature, humidity, and pressure. All these parameters were measured using a sensor and then processed by a microcontroller. Data from the microcontroller is sent to edge computing via RS 485 communication with Modbus protocol. To get valid results, not only the data from the measurements but also combined with the data from the datasheet for each type of battery. All of this data will be combined and become a reference in determining SoC and SoH. The benefit of this research is to help determine which battery will decrease SoC and SoH so that the owner can perform predictive maintenance. Broadly, the benefits of research in the area of data center battery management, BTS for on-grid areas.